SEPARATION AND PRECONCENTRATION OF COPPER (II) ION BY FATTY HYDROXAMIC ACIDS IMMOBILIZED ONTO AMBERLITE XAD – 4 RESIN - Dedy Suhendra; W. M. Z. Wan Yunus; Md. Jelas Haron; Mahiran Basri; Sidik Silong (Indonesian Journal of Chemistry, 2006)
A method of copper (II) ion preconcentration and separation from other ions by using a column containing fatty hydroxamic acids - loaded Amberlite XAD 4 resin (FHA-Amb) is described. Several factors, which affect the separation and preconcentration efficiency such as pH, sample volume, and concentration of eluent and flow rate, have been investigated.  A quantitative recovery of copper (II) ion from FHA-Amb resin column was obtained using 10% HNO3 solutions as eluent with a preconcentration factor of 60. A method for separation of Cu(II) from Zn(II) and Cd(II) is proposed.  A rapid sample throughput, a clean separation, a high preconcentration factor and simplicity are the main advantages in these analytical procedures.